Isolation, characterization and identification of an As(V)-resistant plant growth promoting bacteria for potential use in bioremediation - Agnihotri, Puja; Banerjee, Sharanya; Maitra, Madhumita; Mitra, Arup K. (Asia-Pacific Journal of Science and Technology, 2021)
Soil is a reservoir of various kinds of bacteria that have several constitutively expressed as well as inductively expressed functions. These bacteria not only have plant growth promoting activities but also often come with added features, such as heavy metal tolerance, nitrogen fixation, iron chelation and plant hormone production. Because arsenic (As) pollution has become a rising global threat, it is important to utilize eco-friendly strategies for As mitigation, such as bioremediation. In the present study, bacterial strains were obtained from the soil of North 24 Parganas, an arsenic polluted district in West Bengal and their As-tolerance was tested under in-vitro conditions. Several bacterial strains were isolated and their arsenate (As(V)) tolerance was studied. Out of these bacteria, the strain S3C2 was found to have the highest tolerance level. Furthermore, this strain was found to retain 40 % of As in the cell pellet from the medium, as revealed by inductively coupled plasma optical emission spectroscopy analysis data. This efficient As(V)-resistant strain was identified using16S rRNA sequencing and was found to be a Bacillus cereus strain (GenBank Accession Number MW012261). It was found to be positive for siderophore production, with the ability to solubilise 19% of phosphate and produce 1.87±3.2 µg/ml indole acetic acid in Tryptophan supplemented medium in vitro. This highly As(V)-resistant plant growth promoting bacterial strain has potential for As mitigation from polluted natural sources and promote the growth of plants in arsenic polluted zones at the same time.